2017
DOI: 10.1007/s00035-017-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Alpine populations of Rhytidium rugosum (Bryophyta) in a European context

Abstract: The phylogeography and possible origins of the moss Rhytidium rugosum (Hedw.) Kindb. in the European Alps are studied based on information from the nuclear internal transcribed spacers 1 and 2 and a portion of the gene region for glyceraldehyde 3-phosphate dehydrogenase for 364 European specimens. Seventy-three Alps specimens were sampled from W Switzerland to W Austria, and were divided into four regional populations along a WestSouth-West (WSW) to East-North-East (ENE) gradient. These populations were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Genetic diversity in the two species was comparable to that in previously studied bryophytes (e.g. Szövényi et al , 2006 ; Hedenäs, 2017 ). Overall, genetic diversity ( H , π n ), the number of effective haplotypes and number of private haplotypes per region were higher in D. turgescens than in D. trifarius .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Genetic diversity in the two species was comparable to that in previously studied bryophytes (e.g. Szövényi et al , 2006 ; Hedenäs, 2017 ). Overall, genetic diversity ( H , π n ), the number of effective haplotypes and number of private haplotypes per region were higher in D. turgescens than in D. trifarius .…”
Section: Discussionsupporting
confidence: 78%
“…Our data thus do not support the third prediction of lower genetic diversity in areas with rare rather than regular sexual reproduction. In D. turgescens , the proportion of genetic variation between regions was significant, albeit limited (4 %; Table 4 ), and was in the lower range of interregional differentiation observed in other plant species ( Zhang et al , 2005 ; Hedenäs, 2017 ). Previous studies of different plant species reported that genetic variation could also be retained in predominantly clonal populations, depending on the colonization history of a species (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One of the possible applications of macrofossil databases is tracing the species distribution dynamics during glacial/interglacial cycles. Many studies have reconstructed glacial refugia and post-glacial recolonization patterns of individual species at the European scale, including bryophytes (Szövenyi et al 2006, Kyrkjeeide et al 2012, Hedenäs 2017. In central and western Europe, there is a long tradition of identifying which of the regionally rare species are relicts from glacial times, or at least from before the middle-Holocene climate optimum (so called 'glacial relicts' in this concept; see Rybníček 1966, Jankovská 1988, Odgaard 1988.…”
Section: Introductionmentioning
confidence: 99%